The COVID-19 pandemic as a destabilizing event: Did it punctuate Thailand’s local budget dynamics? - Chuayprakong, Pawinee (Humanities, Arts and Social Sciences Studies, 2025)
Current studies state that budget dynamics in many developed countries have followed the assumptions of the Punctuated Equilibrium Theory. However, the budget dynamics of developing countries remain inadequately examined. This research, which concentrates on public health spending in Thailand’s local government, serves as a theory-testing case study to confirm the Punctuated Equilibrium Theory’s external validity. Integrating with the focusing events of the Multiple Streams Framework, this study examines whether and how the COVID-19 pandemic punctuated public health spending among sixty-eight Thai local governments at the provincial level during 2013–2023, covering three timeframes—up until the first year of, during, and after the COVID-19 pandemic. The descriptive statistics portraying the data’s leptokurtic distribution confirm that, over a lengthy period, the local public health spending followed the Punctuated Equilibrium Theory and featured a policy stasis which was occasionally interrupted by budget punctuations or large-scale departures from the past. Meanwhile, the results from the Chi-Square test and ANOVA underscore the statistically significant association between the arrival of the COVID-19 pandemic and the surge in the number of positive punctuations. These findings reject the default assumption that budget dynamics are incremental, especially for long-term policy analysis. Instead, they urge local policymakers to be actively aware of focusing events and to constantly (re)build fiscal competency to guarantee a smooth and effective response and recovery plan when a locality faces crises or impactful occurrences.